(untitled) (Research, Society and Development, 2020)
The present study aimed to contain the eroded soil and runoff water proved superficially in the hillside area within the Governador Valadares campus of the Federal Institute of Minas Gerais. In a total area of approximately 43.125 m2, which for financial operations divided into five areas.The results from the intervention at the 4 export points, the same being three new dam sand cleaning of two other existing ones, in addition to the installation of 18 palisades; in addition, the planting of 742 vetiver grass seedlings at critical points in the basin, where the soil was exposed and culminated in a 265 m3 water storage capacity in the barraginhas. In the period from September 2018 to April 2019, there was 853.9 mm of rain and it is estimated that approximately 70% of this volume remained retained by the barraginhas Approximately 20 m3 of sediment were also retained in the barraginhas. Approximately 50% of the vetiver grass seedlings survived. The total cost of the project, except labor, was R 4,645.80, considering the successful values for water production and mitigation or sediment input in the drainage channels that use the downstream of the intervention area.